Caste in the swarming wasps: 'queenless' societies in highly social insects - Noll, Fernando Barbosa [UNESP]; Wenzel, John W. (Wiley-Blackwell, 2008)
Morphometric data for 30 species of swarming wasps (Vespidae: Polistinae: Epiponini) are presented, representing all currently recognized genera. Data are coded according to whether females that were shown by dissection to be egglayers are larger, similar, or smaller for each dimension than non-egglayers. These data are analysed in a phylogenetic framework with primitively social Polistes and Mischocyttarus as outgroups. Representative measurements are illustrated to show that most genera of Epiponini appear to have ancestry in a lineage that has no queen caste comparable with either the primitively social outgroups, or the more derived species of the tribe. This analysis indicates that a conspiracy of workers that operates without a queen characterizes the societies of many Epiponini, or their recent ancestors. (c) 2008 The Linnean Society of London.
Keywords: cladistics; Epiponini; Hymenoptera; morphological differences; neotropical wasps; Phylogenetics; Vespidae